W. E. B. Du Bois' Africa : scrambling for a new Africa - Adé, Taharka (Anthem Press, 2023)
W. E. B. Du Bois was one of the leading figures of Pan-African thought and activism in the twentieth century. This book delivers for the first time a comprehensive Afrocentric investigation and critique of Du Bois's writings on Africa and Pan-Africanism.